Left atrial morpho-functional changes in hypertrophic cardiomyopathy and Fabry disease: a CMR-feature tracking study. (13th July 2021) - Moroni, A; Tondi, L; Camporeale, A; Milani, V; Pica, S; Pieroni, M; Pieruzzi, F; Ferri, L; Arosio, R; Chow, K; Lombardi, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left ventricular (LV) diastolic dysfunction (DD) is a hallmark of hypertrophic cardiomyopathy (HCM) and its phenocopies, such as Fabry disease (FD). Together with left atrial (LA) size, LA function is emerging as a sensitive marker of the adaptive changes to backward transmission of LV cardiac filling pressure, thus implementing DD assessment. Additionally, both HCM and FD are characterized by a primitive atrial myopathy, but LA morpho-functional changes in HCM and FD have never been directly compared. More recently, LA strain by Cardiovascular Magnetic Resonance Feature Tracking (CMR-FT) has been demonstrated to be a feasible and reproducible tool to explore LA function. Purpose: To compare LA morpho-functional changes in HCM and FD and to explore their correlation with tissue alterations. Methods: 15 HCM and 15 sex-, age- and LV mass index-matched FD patients underwent CMR (Magnetom Aera 1.5T, Siemens) and Doppler Echocardiography for LV diastolic function assessment (E/e' and DD grading from 0 to 3). LA phasic function was evaluated by CMR-FT strain (Qstrain Medis). The software output included passive (εe, conduit function), active (εa, booster pump function) and total strain (εs, reservoir function), along with LA volumes and ejection fraction (EF). Late gadolinium enhancement (LGE) was quantified as a percentage of LV mass using the standard deviations (SDs) method (≥ 5 SDs). Interstitial fibrosis was assessed by extracellular volume (ECV) quantification in remote myocardium. All patients were in sinus rhythm. Results: In the HCM group, the proportion of patients with DD grade 2-3 was only slightly higher than in FD (p 0.26). Accordingly, no significant difference was found in E/e' value (p 0.78). Compared to FD, HCM patients showed more severe LA morpho-functional changes, including larger LA end-systolic volume (ESV) (113 ± 35 vs 84 ± 23 ml), lower LA EF (37 ± 7 vs 44 ± 9 %) and a greater reduction of εs (-20 ± 5 vs -25 ± 6 %) and εa (-10 ± 4 vs -15 ± 4 %) (all p < 0.05). LV size and function and the burden of fibrosis (LGE quantification and ECV) were comparable between the two groups. Interestingly, in HCM population, unlike in FD, LA morpho-functional measurements significantly correlated with tissue characterization parameters (LA ESV with LGE, r 0.56, p 0.03; εs and εa with ECV, r -0.51, p 0.05 and r -0.59, p 0.02, respectively). Conclusions: LA morpho-functional alterations are much more severe in HCM compared to FD with similar degree of LV hypertrophy. A more severe atrial myopathy or different mechanisms of atrial damage in the two cardiomyopathies may explain these findings. LA CMR-FT analysis may represent a sensitive tool to discriminate between HCM and FD, although larger studies are needed to confirm this finding and the possible correlation with the occurrence of atrial arrhythmias and thromboembolic risk.